Latin-America working children situation (2019)
This text provides an overview on child labor in Latin America and the inability to compute accurate statistics on the phenomenon. The latter, because it is seen as a scourge which is, not only more common than desired, but also domestic and unpunished. It also takes us through the various international estates formed to advocate for children and fi nally it is concluded that it is necessary to increase awareness, union, and investment for the protection of minors